2010
DOI: 10.1186/1742-2094-7-73
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokines derived from West Nile virus (WNV)-infected SK-N-SH cells mediate neuroinflammatory markers and neuronal death

Abstract: BackgroundWNV-associated encephalitis (WNVE) is characterized by increased production of pro-inflammatory mediators, glial cells activation and eventual loss of neurons. WNV infection of neurons is rapidly progressive and destructive whereas infection of non-neuronal brain cells is limited. However, the role of neurons and pathological consequences of pro-inflammatory cytokines released as a result of WNV infection is unclear. Therefore, the objective of this study was to examine the role of key cytokines secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
128
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 74 publications
(156 reference statements)
8
128
1
1
Order By: Relevance
“…TNF-α impairs glutamate uptake by astrocytes, leading to neuronal death due to excitotoxicity [197]. Consistent with this, it has been shown that increased expression of TNF-α after infection with WNV and JEV is correlated with neuronal death [154,195], and that neutralizing antibodies specific for IL-1β and TNF-α protected neurons from WNV-induced cell death [195]. The release of inflammatory cytokines by neurons can trigger gliosis (i.e., microglial and astrocyte activation), which is one of the major hallmarks of arboviral neuropathogenesis [154,186,198].…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 75%
See 2 more Smart Citations
“…TNF-α impairs glutamate uptake by astrocytes, leading to neuronal death due to excitotoxicity [197]. Consistent with this, it has been shown that increased expression of TNF-α after infection with WNV and JEV is correlated with neuronal death [154,195], and that neutralizing antibodies specific for IL-1β and TNF-α protected neurons from WNV-induced cell death [195]. The release of inflammatory cytokines by neurons can trigger gliosis (i.e., microglial and astrocyte activation), which is one of the major hallmarks of arboviral neuropathogenesis [154,186,198].…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 75%
“…Following CNS infection by arboviruses, both infected target cells and bystander cells release an array of chemokines and proinflammatory cytokines, which trigger neuroinflammation. Neurons release several inflammatory cytokines, such as interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and IL-6 in response to infection by encephalitic flaviviruses, such as WNV and JEV [195]. As well as impairing BBB integrity [152], elevated levels of IL-1β can induce cell cycle arrest and apoptosis in neural precursor cells (NPCs) [196].…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is circumstantial evidence that astrocytes contribute to the second wave of WNV neuroinvasion through the upregulation of MMPs, which disrupt the BBB, and proinflammatory cytokines, which recruit infected leukocytes (5,41,52,53). Indeed, propagation within astrocytes, neurons, and glial cells prior to the breakdown of the BBB is believed to be a common strategy of neuroinvasive viruses, including tick-borne encephalitis virus and HIV, to enhance dissemination within the CNS (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of TLRs in neurons produces a very low level of pro-inflammatory cytokines [11,38,39] , while microglia and astrocytes secret large amounts of cytokines [40,41] . The low level of cytokine production by neurons seems unlikely to induce a global innate immune response in the brain.…”
Section: Innate Immune Responses Of Cns Cells: Neurons Versus Gliamentioning
confidence: 99%